Algebraische Zahlentheorie: 3.8. bis 9.8.1986 - Jehne, Wolfram; Leopoldt, Heinrich-Wolfgang; Roquette, Peter (Tagungsbericht, 1986)
J. A. Antoniadis, Iraklio; G. Frey, Saarbrücken; J. Brinkhuis, Rotterdam; W.-D. Geyer, Erlangen; J. Buchmann, Columbus; G. Gras, Pesmes; Chr. Deninger, Regensburg; B. W. Green, Stellenbosch; G. R. Everest, Norwich; R. Greenber, Seattle; G. Frei-Imfeld, Ste-Foy; D. Haran, Erlangen; U. Jannsen, Regensburg; Franz-Viktor Kuhlmann, Heidelberg; M. Jarden, Tel Aviv; E. Lamprech, Saarbrücken; W. Jehne, Köln; J. B. Leicht, Heidelberg; E. Kani, Heidelberg; H. W. Leopoldt, Karlsruhe; N. Klingen, Köln; A. Leutbecher, München; W. Kohnen, Bonn; J. J. Liang, Tampa; F. Lorenz, Münster; J. Neukirch, Regensburg; B. H. Matzat, Karlsruhe; R. W. K. Odoni, Exeter; T. Metsänkylä, Turku; H. Opolka, Göttingen; B. Z. Moroz, Bonn; M. Pohst, Düsseldorf; W. Narkiewcz, Marburg; Florian Pop, Heidelberg; Brigitte Nebelung, Köln; A. Prestel, Konstanz; J. Queyrut, Talence; N. Schappacher, Göttingen; H. P. Rehm, Karlsruhe; R. Schertz, Augsburg; C. R. Riehm, Burlington; A. Schnizel, Warschau; P. Roquette, Heidelberg; C.-G. Schmidt, Bonn; N. Sankaran, Chandigarh; G. Tamme, Regensburg